Podcasts as Digital Narratives for Higher Education: Enhancing Engagement and Reflective Learning - Baharuddin Baharuddin; Clara Mendes; Dyah Retno Wulan; Erni Hastuti; Livia Alves (Yayasan Adra Karima Hubbi, 2025)
Background. The integration of digital media in higher education has redefined how students engage with learning materials and construct reflective understanding. Podcasts, as a form of digital narrative, provide flexible, accessible, and multimodal learning experiences that foster critical thinking and personal connection with content. Purpose. This study aims to explore how educational podcasts enhance student engagement, promote reflective learning, and support independent knowledge construction in higher education. Method. Using a qualitative mixed-method design, data were collected from 120 university students through surveys, focus group discussions, and reflective journals. Thematic and descriptive statistical analyses revealed that podcasts significantly increased learners’ motivation, concentration, and comprehension of complex concepts. Students reported that the narrative and conversational tone of podcasts stimulated reflective thinking and emotional engagement, making learning more meaningful and personalized. Results. The results also indicated that integrating podcasts into coursework encouraged continuous learning beyond the classroom and improved retention through self-paced listening. Conclusion. The study concludes that podcasts function not only as instructional media but also as digital narratives that humanize learning by merging information delivery with reflection and storytelling.